2017
DOI: 10.2135/cropsci2016.05.0377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trinexapac‐Ethyl and Daconil Action (Acibenzolar‐S‐Methyl and Chlorothalonil) on Heat and Drought Tolerance of Creeping Bentgrass

Abstract: The plant growth regulator trinexapac‐ethyl (TE) is known for its effects of suppressing shoot vertical growth. Some fungicides are claimed to promote the physiological health of plants in the absence of diseases. The objective of this study was to determine whether acibenzolar‐S‐methyl (one of the active ingredients in Daconil Action), TE alone, or the combination of the two may be most effective in promoting creeping bentgrass (Agrostis stolonifera L.) tolerance to heat and drought stress under field conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…A number of metabolic pathways induced by ASM during pathogen attack, including anti-oxidant metabolism, have also been demonstrated to be activated during abiotic stress ( Soylu et al, 2003 ). Several recent studies under field conditions have demonstrated that ASM improved heat and drought tolerance in creeping bentgrass ( Shekoofa et al, 2015 ; Jespersen and Huang, 2016 ), and the improved drought performance of creeping bentgrass was associated with ASM-reduction of transpirational water loss ( Shekoofa et al, 2015 ). The mode of action for ASM regulation of abiotic stress tolerance is still unclear and how it alters metabolic pathways to improve stress tolerance is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…A number of metabolic pathways induced by ASM during pathogen attack, including anti-oxidant metabolism, have also been demonstrated to be activated during abiotic stress ( Soylu et al, 2003 ). Several recent studies under field conditions have demonstrated that ASM improved heat and drought tolerance in creeping bentgrass ( Shekoofa et al, 2015 ; Jespersen and Huang, 2016 ), and the improved drought performance of creeping bentgrass was associated with ASM-reduction of transpirational water loss ( Shekoofa et al, 2015 ). The mode of action for ASM regulation of abiotic stress tolerance is still unclear and how it alters metabolic pathways to improve stress tolerance is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate acid is an important component of several pathways and links amino acid and respiration metabolism together by serving as a precursor of proline and arginine and converting to and from α-ketoglutarate in the TCA cycle [17]. The accumulation of glutamate in leaves of creeping bentgrass (Agrostis stoloniferaand) tall fescue (Festuca arundinacea) has been positively correlated with heat and drought tolerance [18,19]. Arginine is an important precursor of nitric oxide and compounds involved in the synthesis of polyamines, participates in various physiological and biochemical processes of plants, and significantly contributes to plant growth, development, and stress tolerance [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the accumulation of amino acids, including aspartic acid, glutamic acid, proline, 5‐oxoproline, and valine, has been positively associated with heat or drought stress tolerance in various plant species, such as reported in creeping bentgrass ( Agrostis stolonifera ) and tall fescue ( Festuca arundinacea ) (Jespersen et al, 2017; Li et al, 2016; Yang et al, 2014; Yu et al, 2012). Increased levels of organic acids, such as malic acid, threonic acid, and shikimic acid, have also been found in plants with improved heat tolerance (Du et al, 2011; Jespersen & Huang, 2017; Yu et al, 2012). Although previous studies have shown that NOL is involved in the induction of leaf senescence, the metabolic factors and associated pathways underlying NOL‐mediated regulation of heat‐induced leaf senescence are unknown.…”
Section: Introductionmentioning
confidence: 99%